Control of Water Flow Rate in a Tank Using the Integral State Feedback Based on Arduino Uno - Hendriyanto, Raeyvaldo Dwi; Puriyanto, Riky Dwi; Ma'arif, Alfian; Vera, Marco Antonio Márquez; Nugroho, Oskar Ika Adi; Chivon, Choeung (Control Systems and Optimization Letters, 2024)
In the industrial world, many tools have been made to facilitate human work in carrying out control and measurement that is made automatically in a production process. Because in some parts of a production process in the industry that is done manually is no longer effective so that accurate and precise automatic control is needed. The control that will be used in this study is the Integral State Feedback (ISF) control with Arduino Uno as a microcontroller to design and run the system. The actuator used is a 12V water pump with the sensor used is the YF-S401. The system will run the ISF control as long as the data is less than 300 and if it reaches 300 data, the system will stop processing the ISF control and turn off the 12V water pump. The sensor reading error obtained is 27%. Parameters Ki = 0.3, K1 = 6, and K2 = 2 obtained from MATLAB Simulink can be applied to the research tool but have a slow system response Delay Time and Rise Time, so the researcher made a modification parameter with a value of Ki = 1, K1 = 6, and K2 = 2 and obtained a faster system response Delay Time and Rise Time. So it can be concluded that the best parameters for this study use modified parameters.